2009
DOI: 10.4319/lo.2009.54.1.0289
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Pseudo-nitzschia and domoic acid in the Juan de Fuca eddy region and its adjacent shelves

Abstract: The Juan de Fuca eddy is a toxic ''hot spot.'' Domoic acid (DA) was detected in the eddy during each of six cruises over a 4-yr study, although Pseudo-nitzschia abundance and toxin concentrations were highly variable. During the September 2004 eddy bloom, Pseudo-nitzschia spp. exceeded 13 3 10 6 cells L 21 , and particulate DA reached 80 nmol L 21 . Of the .10 species of Pseudo-nitzschia identified in this region, those coincident with the most toxic blooms are P. cf. pseudodelicatissima, P. cuspidata, P. mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
82
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 34 publications
1
82
3
Order By: Relevance
“…This was emphasized by Marchetti et al (2004), who in their field study concluded that environmental factors other than those studied so far (mainly related to nutrient stress) need to be examined to understand DA production in Pseudo-nitzschia species. Trainer et al (2009) supported this view by stating that, under natural conditions, macronutrients cannot be used as reliable predictors of toxicity of a Pseudo-nitzschia bloom. Our study shows that zooplankton grazing could be one of the factors controlling the toxicity of a Pseudo-nitzschia bloom in the field.…”
Section: Discussionmentioning
confidence: 60%
“…This was emphasized by Marchetti et al (2004), who in their field study concluded that environmental factors other than those studied so far (mainly related to nutrient stress) need to be examined to understand DA production in Pseudo-nitzschia species. Trainer et al (2009) supported this view by stating that, under natural conditions, macronutrients cannot be used as reliable predictors of toxicity of a Pseudo-nitzschia bloom. Our study shows that zooplankton grazing could be one of the factors controlling the toxicity of a Pseudo-nitzschia bloom in the field.…”
Section: Discussionmentioning
confidence: 60%
“…The linkages between DA production and environmental factors such as macronutrients, trace metals, temperature, and salinity are also complex and variable (16). It is likely the case that no one single environmental variable is a strong predictor of DA (27); hence a mechanistic explanation behind cellular-level DA production and elevated DA in shellfish during warm ocean regimes is outside the scope of this study given the data we have. Even so, our findings frame future work investigating DA production by Pseudo-nitzschia in the context of conditions associated with warm regimes, for example, monitoring changes in species composition over time to investigate whether distinctive "warm" Pseudo-nitzschia assemblages indeed cooccur with copepod community shifts.…”
Section: Discussionmentioning
confidence: 76%
“…These events support the hypothesis that up-regulation of DA, and/or enhanced growth of toxigenic Pseudo-nitzschia is favored during the transition from warm to cool regimes. Warm ocean regimes potentially affect Pseudonitzschia species abundance and toxicity in an array of ways, from cellular and metabolic processes that are sensitive to elevated temperatures to larger-scale changes in phenology, water column structure, and circulation patterns (27,34). The linkages between DA production and environmental factors such as macronutrients, trace metals, temperature, and salinity are also complex and variable (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DA is transferred through food-web interactions, and can affect the ecosystem over large spatial and temporal scales. DA has been detected in marine consumers ranging from copepods to mollusks, fish, and mammals (Doucette et al 2006;Caron et al 2010), and ASP toxicity events have greatly increased in both frequency and intensity over the last decade along the U.S. West Coast (Scholin et al 2000;Trainer et al 2000). In California waters, outbreaks of DA poisoning from toxic Pseudo-nitzschia spp.…”
mentioning
confidence: 99%